Association of long interspersed nucleotide element‐1 and interferon regulatory factor 6 methylation changes with nonsyndromic cleft lip with or without cleft palate. (25th September 2018) - Li, Yanhua; Deng, Ying; Deng, Changfei; Xie, Liang; Yu, Li; Liu, Lijun; Yuan, Yumei; Liu, Hanmin; Dai, Li
Abstract: Objective: To examine the possible associations between methylation changes in the promoter regions of long interspersed nucleotide element‐1 (LINE‐1) and interferon regulatory factor 6 gene ( IRF6 ) and nonsyndromic cleft lip with or without cleft palate (NSCL/P). Methods: A case–control investigation was performed to compare 37 infants affected by NSCL/Ps with 60 babies without cleft malformations. Their genomic DNA samples were obtained, and the LINE‐1 and IRF6 methylation levels were measured by using Sequenom MassArray. Unconditional logistic regression was adopted to estimate the odds ratio. Results: Infants with NSCL/Ps had a higher methylation level at LINE‐1 and IRF6 promoter regions than controls. High levels of LINE‐1 (≥64.07%) and IRF6 (≥6.46%) methylation were associated with an increased risk of NSCL/P (LINE‐1, OR = 2.63, 95% CI: 1.07–6.57; IRF6, OR = 4.73, 95% CI: 2.10–13.07), and the associations remained to be significant after adjusting for potential confounders. Similar associations were also found for cleft lip only, cleft lip, and palate. Conclusion: Our study suggested that aberrant methylation of LINE‐1 and IRF6 might contribute to the development of NSCL/Ps. Further studies are needed to replicate the findings.